Pengendalian hama ulat penggulung daun pisang (Erionota thrax L.) dengan ekstrak kasar batang sereh (Cymbopogon citratus) - Mudasir Mudasir; Sugiyanto Sugiyanto; Fetty Dwi Rahmayanti (University of Insan Cendekia Mandiri, 2025)
Lemongrass stems (Cymbopogon citratus) are natural ingredients that contain allelopathic compounds, which can disrupt the metabolic processes of pests, which can cause death. Kitchen lemongrass stems can be used as a preference, as a natural, environmentally friendly ingredient for controlling banana leafroller caterpillar pests (Erionota thrax L). This study aims to determine the effect of kitchen lemongrass stem extract on the time of death of E. thrax larvae, to obtain the best concentration and dose as well as the interaction of determining the concentration and dose of the extract on time of death, mortality, body condition and percentage of attacks by Erionata thrax L larvae. The research method used a Factorial Completely Randomized Design (CRD) consisting of 2 factors with 4 treatments and 4 repetitions. The 1st factor is the concentration (20%, 40%, 60% kitchen lemongrass bioinsecticide) and 1% (1% insecticide) while the second factor is the dose of 10 ml, 20 ml and 30 ml of kitchen lemongrass stem extract. The observation data was analyzed using ANOVA (Analysis of Variance) at the 5% level. If there is a real influence, then proceed with the LSD (Least Significant Difference) test. This research shows that the application of lemongrass stem extract has a real influence on the time of death, larval mortality, body condition, and percentage of appetite of banana leafroller caterpillars. A concentration of 60% and a dose of 30 ml of lemongrass stem extract provided a significant interaction with the death time of Erionata thrax L larvae.